The quality of environmental, social and corporate governance information reported by South African listed companies - Ncube, Lethukuthula (Rhodes University, 2026)
Environmental, social and governance (ESG) reporting has emerged as a crucial tool to provide stakeholders with transparent, decision-useful information about companies' environmental impacts, social practices and governance structures in South Africa's corporate sector. As stakeholder demand for comprehensive ESG disclosures intensifies, these reports have become essential instruments for investment decisions, regulatory compliance and corporate accountability. However, the effectiveness of ESG reporting in accurately conveying corporate performance is increasingly undermined by a central tension: the competing imperatives of comprehensive disclosure and corporate image management. Companies must navigate between meeting stakeholder expectations for transparency while simultaneously managing reputational risks and competitive positioning. This tension significantly shapes corporate reporting behaviour. Research suggests that many South African firms prioritise reputation enhancement in their ESG reports over providing a balanced and complete account of their performance. This often results in selective disclosures where unfavourable information is downplayed or omitted, creating a discrepancy between reported and actual ESG impacts. Such practices compromise stakeholders' ability to assess organisations' true ecological, societal and governance impacts, raising serious concerns about the credibility and transformative potential of ESG reporting in driving meaningful corporate reform. Despite the growing recognition of these challenges, there remains a critical gap in methodologies used to rigorously evaluate the quality of corporate ESG disclosures. In response, this thesis develops a model to assess two core qualitative characteristics of ESG disclosures by South African listed companies: their relevance for stakeholder decision-making and their faithful representation of actual corporate ESG performance and impacts. To develop this model, stakeholder and legitimacy theories are synthesised into an integrated theoretical framework. This framework guides the identification of key corporate disclosure practices that are hypothesised to influence the quality of corporate ESG reporting among companies listed on the Johannesburg Stock Exchange (JSE). To measure these disclosure practices empirically, a comprehensive set of quantifiable ESG indicators is selected to operate as observable proxies. Principal Component Analysis (PCA) examines how these theoretically derived ESG indicators cluster and vary, revealing underlying patterns and relationships. These PCA insights inform the selection of independent variables for a binary logistic regression model. In this model, low ESG reporting quality serves as the dependent variable, measured by the presence of corporate ESG controversies. The occurrence of controversies is conceptualised as an external indicator of potential deficiencies in either or both the relevance and faithful representation of corporate ESG reporting. The final model specification, which was developed using ESG data from 2013 to 2018 and validated against 2019 data, reveals a statistically significant inverse relationship between South African listed companies' self-reported adoption of environmental and social policies and the quality of their corporate ESG reporting. Specifically, companies with higher levels of self-reported environmental and social policy adoption demonstrate lower ESG reporting quality, as evidenced by their increased involvement in ESG controversies. These results suggest that such policy declarations may not faithfully represent actual environmental and social performance and may lack relevant information content for stakeholders. In contrast to the inverse relationship found with self-reported policy adoption, board skill diversity did not show a statistically significant relationship with corporate ESG reporting quality. Consequently, this study finds that extensive ESG policy disclosures may function primarily as a legitimacy-seeking mechanism, with companies using policy declarations symbolically to project responsible corporate citizenship rather than demonstrating genuine commitment to implementation. This reporting behaviour reflects a prioritisation of ceremonial compliance with institutional pressures over substantive reporting of underlying operational realities.
Keywords: Uncatalogued